Konsep Bunga Dan Prinsip Ekonomi Islam Dalam Perbankan Syariah - Abdul Rahim (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
Interest is an additional charging on the transaction of money loan that can be calculated in primarily loan without considering the benefit of this loan. Now days, Muslims could not avoid their selves from muamalah with the conventional banks who use the system of interest in all aspects of life, including their religious life and primarily their economic life. Nevertheless, Islamic banking is expected to avoid the application of the interest system and consistency in applying the mudhrabah system. Therefore, where the mudarabah system is a business cooperation agreement between the two parties, in which the first party provides the overall of capital, while others become managers. Mudarabah business profits are divided according to the contract agreement, whereas if the loss, responsible by the owners of the capital as long as the loss is not due to negligence of manager. Had the losses caused by fraud or negligence of the manager, then the manager should be responsible for the losses. Therefore, Islamic banks also apply Wadi'ah system which can be interpreted as a pure deposit of one party to the other, both individuals and legal counsel entities that must be preserved and restored anytime depositors’ wills. Therefore, Islamic economic principles which have been applied in this case are Mudarabhah, Musharakah, and Murabahah.